Social Welfare Analysis: An Economic Study Of Human Development Index, Income Inequality And Poverty In The Provinces Of Aceh And North Sumatera - Fadiya, Feny; Manurung, Mahlina Putri; Saajidah, Annisah; Nasution, Armin Rahmansyah; Pratiwi, Audina; Silaban, Krisnawati; Sirait, Melani Manginar (Jurnal Ekonomi Balance, 2024)
This study was conducted with the aim of knowing how much social inequality occurs between Aceh province and North Sumatra province. The method in collecting and processing data uses descriptive qualitative, where the data obtained is described through graphs as a measure of inequality. The samples in this study are; Human Development Index, Net Income and poverty. The results of this study are 1) The Human Development Index is at an unequal point where North Sumatra province is below Aceh province. 2) Through the net income graph, North Sumatra province is dominantly higher than Aceh province. 3) The poverty index of Aceh province is greater than that of North Sumatra province. 4) Through the processed data, North Sumatra province has superior inequality than Aceh province with two samples that are larger. Based on this research, the author makes a suggestion for the government to increase the policy of increasing employment for regions that do not have large revenues, and pay more attention to the efficiency of fiscal policies that have a direct impact on poverty.